Thermo-catalytic reforming of sewage sludge and hydrogenation of resulting tcr®-oil – a route to renewable chemicals and fuels - Grunwald, Jan; Apfelbacher, Andreas; Hornung, Andreas; Daschner, Robert (European Biomass Conference and Exhibition Proceedings, 2020)
Due to the Paris climate change agreement, new pathways are required to minimize the CO2 emissions. Therefore, the replacement of fossil fuels and reduction of CO2 are important aims. Relating to these circumstances, the use of waste biomass as a resource for fuels and chemicals offers an opportunity to gain bio-products without using crops from farmable land. The so-called Thermo-Catalytic Reforming process (TCR®) is able to produce a high quality organic liquid from waste biomass. In contrast to the established fast pyrolysis liquids, the TCR®-oil offers considerable advantages like low water content (< 2%), low oxygen content (< 5%), and consequently, a low total acid number (< 5 mgKOH/g). The most crucial advantage, the thermal stability of the TCR®-oil, allows thermal downstream processing by refining. Based on the TCR® process and the unique properties of the generated TCR®-oil, a selfsustained bio-refinery concept has been developed. The bio-refinery would include the utilization of residue biomass for heat, power, chemicals, and fuels. In addition to the thermochemical conversion of biomass, a key downstream component of this concept is catalytic hydrogenation of the TCR®-oil. This ensures the removal of heteroatoms like nitrogen, sulfur, and oxygen in order to generate high quality renewable hydrocarbons with properties similar to fossil fuel. The upgrading step is in the focus of this research report. For optimization and scale up of the hydrogenation process, different catalyst tests under varying process conditions were carried out in a lab scale batch reactor. The overall bio-refinery approach will be presented with a more detailed focus on hydrogenation.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Bio-oil; Bio-refinery; Catalytic hydrogenation; Refining; Thermo-chemical conversion